Modelación hidráulica de la red de distribución de agua potable de la parroquia El Retiro, cantón Machala, provincia El Oro. - Bravo Quezada, Adriana Lisseth (2017)
The present work of titration aims to analyze the present situation that presents the potable water network of her parroquia El Retiro; and to be able to raise appropriate solutions, making the entire community able to supply itself with this vital liquid, that's why it's important to apply hydraulic modeling to the existing water distribution network; The program will enter information taken in the field, That will serve to let us know the flaws that presents this project. An interview was made to the administration of the parish government El Retiro, about drinking water distribution, who knew that the pipes were built thirty years ago, and at the furthest places of the parish the withdrawal the water arrives frequent at night For the analysis of this project, A field survey was conducted to check the connections of the meters at home, research at the board of Potable water to know the water consumption that the community presents in a period of six months, Field research to identify the diameter of pipes and accessories presented by the Potable water distribution network, Topographic surveys of sites were requested from the GAD. Municipal of Machala, and For scientific support in the drafting of the review of journals such as Scielo, Dialnet, Sciencie Direct y Redalyc. To link the digital plans of the sites the parish header El Retiro, EL Recreo, San Vicente y Guarumal 1, facilitated by the autonomous government decentralized Municipal of Machala, you had to take the coordinates at fixed points by using GPS by the margin of error that presents. To know the water consumption that keeps the population in a day, field work was carried out, which consists of the taking of readings of the elevated tank, that is to say, See every hour which is the height of the elevated tank when the community consumes the wáter, And with that get the area, volume and flow per hour. The reading was also made with three manometers at ten selected points of the sites the parish headboard El Retiro, EL Recreo, San Vicente y Guarumal 1, the purpose is to know the pressure that really exists, and with it you know if the water reaches these sites. The project applied the software EPANET, that performs simulations in prolonged periods of hydraulic behavior, Results that will help to detect the pressures in different knots of the network, If there are low and high pressure areas; And if there are sectors that do not reach wáter. By hydraulic modeling in the parish Potable water distribution network El RETIRO, Pictures of the results obtained are shown, analyzing the current situation of the networks where they are evaluated as irregular, because in the distant knots of the system it lacks pressure and does not continuously supply to the sites, San Vicente y Guarumal 1, It is recommended that a storage tank be built in these sites so that the community can supply itself with this vital liquid.